Implementation of the COBIT 2019 Framework on Information Technology Governance and Risk Management (Study Case: CV. Syntax Corporation Indonesia) - Mar'atus Solikhah; Lena Magdalena; Muhammad Hatta (Eduvest - Journal of Universal Studies, 2024)
CV. Syntax Corporation Indonesia is one of the companies that has adopted the application of information technology. In the process of its implementation, CV. Syntax Corporation Indonesia has not yet had an assessment that became an evaluation process of the management or application of information technology in it. Therefore, an assessment process is needed on the governance and management of the information technology it adopts. To support the assessment process, it is assisted by a framework that can be used as a tool during the assessment process, namely using COBIT 2019. The research method used is a qualitative-descriptive method that can describe an event that is happening now through measurement. APO12 and BAI09 sub-domains were obtained based on the mapping results. From the mapping results on the RACI chart and capability level, APO12 is at level 3. As for BAI09, it is at level 2. From the mapping process to the strategic objectives of CV. Syntax Corporation Indonesia has a main focus, namely governance on services and a focus on risk management. This result will form a Critical Success Factor (CSF) which will be a direction in providing recommendations as advice given. On the other hand, there is also a website in the form of a dashboard which is a tool to visualize the results of this assessment process.